2016
DOI: 10.5194/amt-9-4655-2016
|View full text |Cite
|
Sign up to set email alerts
|

Phosgene in the UTLS: seasonal and latitudinal variations from MIPAS observations

Abstract: Abstract. The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) is a Fourier transform spectrometer that measured mid-infrared atmospheric limb emission spectra from July 2002 to April 2012 on board the polarorbiting satellite ENVISAT. We have used MIPAS data to study the latitudinal variations of phosgene (COCl 2 or carbonyl chloride) and, for the first time, its seasonal variation in the upper troposphere/lower stratosphere region (UTLS). Retrievals of phosgene were made using the 830-860 cm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It was noted in the original ACE‐FTS study (Fu et al, ) that the phosgene retrieval uncertainty is dominated by spectroscopic errors, assumed to be ∼30%, resulting from uncertainties in line intensities and the lack of hot bands in the linelist. A recent MIPAS phosgene data set (Valeri et al, ) used a new and improved spectroscopic linelist for phosgene. The upper tropospheric values are comparable to those of the ACE‐FTS, although it needs to be recognized that this was an optimal‐estimation scheme making use of ACE‐FTS profiles as the a priori.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted in the original ACE‐FTS study (Fu et al, ) that the phosgene retrieval uncertainty is dominated by spectroscopic errors, assumed to be ∼30%, resulting from uncertainties in line intensities and the lack of hot bands in the linelist. A recent MIPAS phosgene data set (Valeri et al, ) used a new and improved spectroscopic linelist for phosgene. The upper tropospheric values are comparable to those of the ACE‐FTS, although it needs to be recognized that this was an optimal‐estimation scheme making use of ACE‐FTS profiles as the a priori.…”
Section: Resultsmentioning
confidence: 99%
“…The first global distribution of phosgene was derived from measurements by the Atmospheric Chemistry Experiment Fourier transform spectrometer (ACE‐FTS)—in total 5,614 vertical profiles between February 2004 and May 2006 were used (Fu et al, ). More recently Valeri et al () used Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) measurements, in particular 28,000 vertical profiles from the 18th and 20th of each month of 2008, to investigate the seasonality and latitudinal distribution of phosgene in the UTLS region.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lower intensity of the measured signal, the individual MIPAS spectra show a lower signal to noise ratio (SNR) than the ACE-FTS ones. Despite the larger noise error of the MIPAS profiles retrieved from single scans, Valeri et al (2016) showed that high-vertical-resolution, goodquality distributions of COCl 2 can be obtained by MIPAS on a per profile basis. Therefore, Valeri et al (2016) were able to study the seasonality and the latitudinal distribution of phosgene based on a restricted set of MIPAS measurements: the data acquired over 2 d month −1 in the year 2008.…”
mentioning
confidence: 95%
“…For the estimation of global data and trends, the ACE-FTS sparse spatial sampling makes the averaging of the occultation data for periods of several months necessary, both to reduce the random error down to acceptable levels and to enhance the density of its coverage. The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) covers the spectral region where phosgene signatures are present; therefore, its measurements can also be used to retrieve the phosgene vertical distribution (Valeri et al, 2016). MIPAS measured the middle-infrared limb emission spectrum of the atmosphere on board the European Space Agency (ESA) Environmental Satellite (EN-VISAT) from 2002 to 2012.…”
mentioning
confidence: 99%
“…Note that, due to recent updates in the MWMAKE algorithm and in its assumed error figures (Dudhia, 2019), the selected MWs are different from those used in the work of Valeri et al (2016). The selection process of the new MWs has removed the strong interference with the CFC−11 emissions found by Valeri et al (2016), enabling the retrieval of COCl 2 as a single target. The optimised vertical retrieval range for COCl 2 has been estimated to be from 6 to 36 km for the FR measurements and from 9 to 54 km for the OR measurements.…”
mentioning
confidence: 99%